Spółki prawa handlowego na tle przepisów ustawy o działalności pożytku publicznego i o wolontariacie - Sobczak, Agnieszka (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: Commercial Law Company as a nongovernmental organization in the Act of Public Benefit Activity and of Volunteer Work. The question of the possibility, and the rationale, of recognizing corporate entities as NGOs is associated with a legal “precedent” where under, in a 2004 decision, the District Court in Wroclaw deemed a limited liability company to constitute an NGO carrying on public utility activity and, accordingly, ruled that is should be interred in the register of public utility organizations. It turns out that, while the views on many issues taken by the NGO sector and by the state have much in common, significant differences of opinion persist. analysis of the pertinent laws brings this text to the conclusion that the Wroclaw court had valid grounds for it decision. The article argues for the amendment of certain provisions of the Act on Public Benefit Activity and on Volunteer Work which they consider to be loopholes.